Effect of Neonatal Treatment With the NMDA Receptor Antagonist, MK-801, During Different Temporal Windows of Postnatal Period in Adult Prefrontal Cortical and Hippocampal Function - Plataki, Maria E.; Diskos, Konstantinos; Sougklakos, Christos; Velissariou, Marouso; Georgilis, Alexandros; Stavroulaki, Vasiliki; Sidiropoulou, Kyriaki (Frontiers in Behavioral Neuroscience, 2021)
The neonatal MK-801 model of schizophrenia has been developed based on the developmental and NMDA hypofunction hypotheses of schizophrenia. This animal model is generated with the use of NMDA receptor antagonist, MK-801, during different temporal windows of postnatal life leading to behavioral defects during adulthood. However, no studies have examined the role of specific postnatal time periods in the neonatal MK-801 (nMK-801) rodent model and the resulting behavioral and neurobiological effects. Thus, the goal of this study is to systematically investigate the role of NMDA hypofunction during specific temporal windows in postnatal life on different cognitive and social behavioral paradigms as well as various neurobiological effects during adulthood. Both female and male mice were injected intraperitoneally (i.p.) with MK-801 during postnatal days 7-14 (p7-14) or 11-15 (p11-15). Control mice were injected with saline during the respective time period. In adulthood, mice were tested at various cognitive and social behavioral tasks. Mice nMK-801-treated in p7-14 show impaired performance in the novel object, object-to-place and temporal order object recognition, the social interaction test and contextual fear extinction. Mice nMK-801-treated in p11-15 only affects performance in the temporal order object recognition, the social memory test and contextual fear extinction. No differences were identified in the expression of NMDA receptor subunits, the synapsin or PSD-95 proteins, either in the prefrontal cortex (PFC) or the hippocampus (HPC), brain regions significantly affected in schizophrenia. The number of parvalbumin (PV)-expressing cells is significantly reduced in the PFC, but not the HPC, of nMK-801-treated mice in p7-14 compared to their controls. No differences in PV-expressing cells (PFC or HPC) were identified in nMK-801-treated mice in p11-15. We further examined PFC function by recording spontaneous activity in a solution that allows up state generation. We find that the frequency of up states is significantly reduced in both nMK-801-treated mice in p7-14 and p11-15 compared to saline-treated mice. Furthermore, we find adaptations in the gamma and high gamma activity in nMK-801-treated mice. In conclusion, our results show that MK-801 treatment during specific postnatal temporal windows has differential effects on cognitive and social behaviors, as well as on underlying neurobiological substrates.